Núcleos de estudos das relações étnico-raciais: encruzilhadas para uma educação antirracista nas escolas da RME-BH - Nesir Freitas da Silva (2023)
The research comes from the ripeness of a political conscience about the necessity to add efforts to the fight anti-racist through the appreciation of the Saberes da Gira (knowledge about the Afro-Brazilian religion) as a legacy for academic production. The relevance of this work consists of the lack of studies about the Núcleo de Estudos das Relações Étnico-Raciais (NERER`s, Core of Studies on ethnic-racial relations) conceiving them as a crossroads for the construction of an anti-racist education in the schools of RME-BH. We look for to understand the information flow between the schools NERER`s and Gerência das Relações Étnico-Raciais (GERER, Management ofethnic-racial relations) and their interfaces to the construction of anti-racist education actions. We noticed an effective interaction between them and a concern about the small number of professionals in this strategic place that comprise multiple functions. With the Saberes da Gira`s methodology we resignify the theoretical structure of the canon together with the knowledge of the Terreiro (space where the rites of Afro-Brazilian cults are celebrated) building our analyze from the Exu`s (religious entity) perspective. We recognize the black woman protagonism in the development of the racial agenda debate at RME-BH and their insurgent character relates them to the Pomba-gira (religious entity). The narratives of our Marias gave life to this study allowing the systematization of movements that culminated in the formation of NERER`s and GERER, contributing to the construction of a policy to promote racial equality. We verify the nucleus as spaces for training professionals on the racial agenda and the construction of anti-racist educational actions. The NERER`s reveled themselves as spaces of resistance against hegemony and fortification of the Racial Equality Promotion Policy. As challenges for the construction of an anti-racist RME-BH were pointed out the low involvement of school management, the emotional distress caused by the weight of protagonism in the racial debate and the need for an institutional approach to these challenges. We understand that the link between the advancement of the policy of promoting racial equality through the construction of an anti-racist education and the understanding of professionals about the political debate inherent to this agenda needs to be developed. We recognize in the systematized movements in the research a progress of the debate on the racial agenda in education, which involves breaking the silence, triggers the dynamics of denouncing racism, advances in building practices to combat racism and is currently going through a propositional moment, through construction of a concept of anti-racist education at RME-BH. However, we believe that greater investment is necessary to reflect on this theme.